Filmgespräch: "Afrikaleidoskop meets ARTE: Sudan – Ein Krankenhaus im Schatten des Krieges " (Afrikaleidoskop meets ARTE, 2026)
As part of the event series “Afrikaleidoscop meets ARTE,” the screening of the ARTE documentary "Sudan – Ein Krankenhaus im Schatten des Krieges" and subsequent discussion took place on October 29, 2025, at 7:00 pm CEST at Kulturhaus Neueinhalb. The evening brought together students, researchers, and members of the wider public for a shared viewing of ARTE’s powerful documentary on Sudan. Since April 2023, Sudan has been devastated by a violent civil war over control of Africa’s third-largest country. More than 25 million people are facing hunger, and around 12 million have been displaced. Hundreds of thousands have fled to the remote Nuba Mountains — a region lacking roads, mobile networks, and adequate medical care. The ARTE documentary follows surgeon Joseph Yacoub, who has run a hospital in the Nuba Mountains for nearly 30 years. As the only surgeon in the region, he treats hundreds of patients every day — from pregnant women and malnourished children to those wounded by the conflict. Together with his team, he works tirelessly to sustain medical care under extreme conditions while training young professionals who may one day carry his mission forward. Following the screening, filmmakers Laura Salm and Carl Gierstorfer joined the audience for a discussion about the making of the film, the challenges of reporting from a remote war zone, and the ethical responsibility of documentary storytelling in times of crisis. The exchange provided deeper insight into the humanitarian situation in Sudan and created space for questions and reflections from the audience. The event was recorded and is also available in ARTE’s media hub.